The Effect of Transformational Leadership and Organizational Culture Through Job Satisfaction and Work Motivation on Employee Performance: Case of PTPN XIV Bone Sugar Factory - Andi Samsir; Abd Muis (International Journal of Educational Administration, Management, and Leadership, 2023)
This study aims to determine and analyze the effect of 1. Transformational leadership has a direct effect on employee job satisfaction at PTPN XIV Bone Sugar Factory. 2. To determine the direct influence of organizational culture on employee motivation at PTPN XIV Bone Sugar Factory. 3. To determine the effect of direct job satisfaction on work motivation at PTPN XIV Bone Sugar Factory. 4.To determine the effect of direct job satisfaction on employee performance at PTPN XIV Bone Sugar Factory. 5. To determine the effect of direct work motivation on employee performance at PTPN XIV Bone Sugar Factory. Data was collected through observation, data analysis, and questionnaires. The research method used is research in the form of descriptive quantitative using Smart PLS 4.0 data analysis techniques. The results of the study show that organizational culture has no significant effect on performance through work motivation, problems that occur in the company because employees still adhere to the old culture, namely that employees are still consistent with the old culture, namely result orientation or in terms of involving the work team in achieving output, in other words If you don't apply teamwork properly to every employee in the company, then superiors should direct more so that employees are consistent with the new culture that exists in the company or involve every employee in achieving output or making good teamwork.